POLA MODELING RELIGIUS ORANG TUA DALAM MENINGKATKAN BACAAN AL-QURAN ANAK DI TAMAN PENDIDIKAN AL-QUR'AN BAITURRAHMAN RIMBO ULU TEBO - Aldi Haryono, Marchel; Hafiq (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the important role of parents as religious role models in improving children's Qur'an reading skills, considering the ongoing gap between learning activities at the Al-Qur'an Education Center (TPQ) and daily practice at home. The purpose of this study is to identify and describe the forms of parental religious modeling applied to improve children's Qur'an reading habits and to analyze the supporting and inhibiting factors that influence their implementation in the family context. This study uses a qualitative approach with a descriptive phenomenological design. Data were collected through participant observation, in-depth interviews, and documentation. Participants consisted of seven parents, seven children, and four Quran teachers at TPQ Baiturrahman Rimbo Ulu Tebo, who were selected through sampling aimed at obtaining in-depth information (Data Rich) Ensuring relevance to the research focus. Data were analyzed using the interactive model of Miles and Huberman, including data reduction, data presentation, and conclusion drawing, while data validity was ensured through triangulation of sources and techniques. The research findings revealed that the role of parents in providing religious role models to improve children's Quran reading ability consists of three main forms: exemplary Quran reading practices by parents, regular Quran reading habits at home, especially after Maghrib prayers, and active parental guidance and supervision during children's study sessions. Supporting factors include strong parental motivation, consistency in daily religious practices, and effective collaboration with TPQ teachers. Conversely, inhibiting factors include excessive use of digital media, limited time and parental inconsistency, children's low learning motivation, and an unconducive social environment